Effectiveness of Skin Traction in Reducing Pain in Patient with Hip Fracture - Muhammad, Bashir; Kakar, Aman Ullah Khan; Ahmed, Wazir; Niamat Ullah; Khan, Badal; Baloch, Tauseef Ghaffar; Ain Ud Din; Kakar, Sana Ullah (Indus Journal of Bioscience Research, 2025)
Introduction: Hip fractures are a significant public health issue due to high morbidity and mortality rates. Skin traction is commonly used in the preoperative management of hip fractures to stabilize the fracture site, reduce muscle spasms, and alleviate pain. This study evaluates the effectiveness of skin traction in reducing pain, its impact on analgesic use, and associated adverse effects. Materials and Methods: A qualitative study was conducted among 100 patients with hip fractures in orthopedic wards of tertiary care hospitals. Pain levels were assessed before and after traction using a numerical rating scale, while analgesic requirements were recorded. The study employed thematic analysis for qualitative data, identifying key patterns and themes related to pain management. Descriptive statistics were used to analyze numerical data, providing insights into pain reduction and analgesic use. This approach allowed for a comprehensive evaluation of patient experiences, enhancing understanding of traction’s effectiveness in pain management for hip fractures in a clinical setting. Results: Skin traction significantly reduced pain levels by 54.1% over 48 hours. The need for opioid analgesics decreased by 43.8% and NSAID use by 23.1%. Adverse effects included skin irritation (12%), pressure sores (5%), and neurovascular issues (3%), with 80% reporting no complications. Conclusion: Skin traction effectively reduces pain and analgesic requirements in patients with hip fractures. Regular monitoring is essential to mitigate potential adverse effects and optimize outcomes.